2010
DOI: 10.1186/1471-2148-10-208
|View full text |Cite
|
Sign up to set email alerts
|

Pleistocene glacial cycle effects on the phylogeography of the Chinese endemic bat species, Myotis davidii

Abstract: Background: Global climatic oscillations, glaciation cycles and the unique geographic topology of China have profoundly influenced species population distributions. In most species, contemporary distributions of populations cannot be fully understood, except in a historical context. Complex patterns of Pleistocene glaciations, as well as other physiographic changes have influenced the distribution of bat species in China. Until this study, there had been no phylogeographical research on Myotis davidii, an ende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…Evidence for refugia in the east and southwestern plateaus of China has been reported by previous phylogeographic studies, e.g. in frogs [13] and in bats [14], [15]. In our study, a refugium in the southwest is indicated by high nuclear diversity observed in septentrionalis, and one in the East by both high mtDNA diversity and an ancient TMRCA estimate for bats in this region.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Evidence for refugia in the east and southwestern plateaus of China has been reported by previous phylogeographic studies, e.g. in frogs [13] and in bats [14], [15]. In our study, a refugium in the southwest is indicated by high nuclear diversity observed in septentrionalis, and one in the East by both high mtDNA diversity and an ancient TMRCA estimate for bats in this region.…”
Section: Discussionsupporting
confidence: 82%
“…This phenomenon had major consequences for latitudinal climatic clines between the east and the west of East Asia [16], and led to the formation of three marked altitudinal steps that also correspond to different ecological zones (see Figure 1 in ref. [15]). Relating this topography to our focal populations, septentrionalis corresponds to the edge of step 1, the Central sinicus population to step 2, and the East sinicus population to step 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These population genetic structures were also supported by the results of an AMOVA with 69.56% variation among regions (Table聽2). Population genetic structure was generally consistent with the known macro-ecological characteristics, with individuals from populations with similar vegetation types, temperature, precipitation and topography recovered in the same lineage [7,18]. The pattern of subdivision into subpopulations could be explained by the influence of environmental characteristics during an extended period of time, and especially be reflected in mtDNA.…”
Section: Discussionsupporting
confidence: 56%
“…Therefore, they would escape from warmer areas by moving toward the top of mountains, which enhanced geological isolation and genetic divergence among lineages. However, previous studies on species in southern China failed to detect such effects of pre鈥怭leistocene climate changes on the phylogeographic pattern (You et al ., ; Zhan et al ., ). One of the reasons is that the evolutionary history of these species is too young to detect long鈥恡erm legacies from their genome.…”
Section: Discussionmentioning
confidence: 99%